Analysis of Income Tax (PPh) Article 21 Calculation: A Case Study of Income Tax Withholding on Permanent Employees' Income - Alfredo Yoyakim Sihombing; Galuh Tresna Murti; Atha Riverly Deska; Shafira Divayanti (Universitas Muhammadiyah Makassar, 2023)
Income Tax (PPh) Article 21 is a type of income tax imposed by the government on income originating from salaries, wages, honorariums, allowances and other payments received by individual taxpayers within the territory of the country. In the tax context in Indonesia, PPh Article 21 has a very important role in generating domestic cash revenues. This revenue is used by the government to finance various national development programs and projects aimed at improving community welfare. Income Tax Article 21 has various elements that need to be understood, including the categories of subject and non-subject to tax, as well as object and non-object of tax. Tax subjects refer to individuals who have the obligation to pay PPh Article 21, while non-tax subjects are people who are not obliged to pay this tax, such as foreigners who do not have income from domestic sources. The tax object in PPh Article 21 is income which is the basis for calculating tax. This includes the various types of income mentioned previously, such as salary, wages, honorarium and allowances. However, there are also other payments that may be included in the tax object, depending on the applicable regulations. The purpose of writing this article is to provide a better understanding of several examples of cases of calculating Income Tax Article 21. In this case, it is important to understand how the income of employees or other income recipients is calculated, including the necessary deductions according to applicable tax regulations. With a good understanding of these regulations, taxpayers can ensure that they fulfill their tax obligations appropriately and efficiently, while ensuring compliance with applicable tax laws. All of this is an important step in supporting national development and equal distribution of prosperity in society.